The effect of mindfulness on negative automatic thoughts in cannabis users: a cross-sectional study - Budak, Funda Kavak; Ersogutcu, Filiz; Yilmaz, Emine (Taylor & Francis Inc, 2021)
Purpose: This study was conducted to determine the effect of mindfulness on negative automatic thoughts in cannabis users. Method: The sample size of this cross-sectional study was determined as 60 patients through power analysis. The study was completed with 81 patients. Descriptive characteristics form, mindful attention awareness scale, and automatic thoughts questionnaire-negative was used as the data collection tools. Results: It was determined that the total mean score of the participants was 32.25 +/- 14.09 (low) on the mindful attention awareness scale and 105.52 +/- 26.63 (high) in the automatic thoughts questionnaire-negative. Mindfulness levels of the participants statistically accounted for negative automatic thoughts by 47% (p<0.05). Conclusion: In the study, it was found that there was a negative correlation between mindfulness and negative automatic thoughts in cannabis users.
Keywords: Dependence; mindfulness; cannabis; automatic thought